Kolaborasi Konsep Ikhlas dan Exchange Behaviorism sebagai Media Interaksi Sosial - Karim, Abdul (FIKRAH, 2017)
This article aims to initiate the integration of sincere concepts and exchange behaviorism as a medium to construct one's mentality. Both concepts are useful in balancing material and spiritual aspects in a person. This study uses a qualitative approach with descriptive analytical methods. The results of this study as well as an auto-critique of Homans theory because the basic George Caspar Homans theory of exchange theory who came from exchange behaviorism was too oriented to the material aspect as a social driver. The results show that the concepts of sincerity and exchange behaviorism cannot be separated because they will have an impact on the partiality of life. Therefore, a necessity in growing the balance of life must pay attention to the material aspects and spiritual aspects.